2022
DOI: 10.1111/jvim.16523
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural arteriovenous fistula in 3 cats

Abstract: Three young adult cats with intermittent spinal hyperesthesia and paraparesis and diagnosed with spinal epidural arteriovenous fistula are described. In all 3 cases, magnetic resonance imaging (MRI) showed focal dilatation of the veins in the epidural space of the thoracic spinal cord, whereas computed tomography angiography (CTA) showed dilatation and enhancement from the intercostal vein to the azygos vein at the same site in the arterial phase. Dorsal laminectomy and occlusion of the interarcuate branches r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…CT was used in combination with MR in three cats with arteriovenous fistulas in the thoracic region of the spinal cord. The authors found that both imaging modalities complemented one another to reach a diagnosis ( 28 ). An angiographic study was not performed in the case reported here.…”
Section: Discussionmentioning
confidence: 99%
“…CT was used in combination with MR in three cats with arteriovenous fistulas in the thoracic region of the spinal cord. The authors found that both imaging modalities complemented one another to reach a diagnosis ( 28 ). An angiographic study was not performed in the case reported here.…”
Section: Discussionmentioning
confidence: 99%